THE ROLE OF METACOGNITIVE AWARENESS IN CRITICAL LITERACY LEARNING ON THE READING COMPREHENSION ABILITY OF ELEMENTARY SCHOOL STUDENTS - Adnin Mutiara; Fahmie Firmansyah; Fazri Yulianto; Rizky Arianty; Irma Sofiasyari (DIDAKTIKA: Jurnal Pendidikan Sekolah Dasar, 2025)
Reading comprehension is a crucial core competency for elementary school students' success, yet many challenges remain in the practice of reading instruction. Learning often focuses on the literal aspect without addressing deeper cognitive aspects, such as critical thinking about texts. Critical literacy, which positions students as active readers, can be a solution in developing reading comprehension skills. This study aims to analyze the role of metacognitive awareness in critical literacy learning on elementary school students' reading comprehension skills. Using a quantitative, explanatory design, this study shows that critical literacy learning positively influences reading comprehension skills. Furthermore, metacognitive awareness plays an important role in mediating this influence, as students with strong metacognitive awareness tend to be better able to understand texts in depth. The analysis results show that critical literacy learning not only improves reading comprehension skills directly but also increases students' awareness of their thinking processes while reading. These findings suggest that a critical literacy approach integrating metacognitive awareness can improve the quality of elementary school students' reading comprehension and have important implications for the development of Indonesian language learning at the elementary level.